Pengaruh Perubahaan ROA, Perubahan OPM, Leverage dan Ukuran Perusahaan Pada Praktik Perataan Laba - Sutaryani, Ni Luh Made; Suardikha, Made Sadha (E-Jurnal Akuntansi; Vol 25 No 2 (2018)DO - 10.24843/EJA.2018.v25.i02.p01, 2018)
The purpose of this study is to be able to determine the effect of changes in ROA, OPM, company size and leverage to the practice of income smoothing. Locations in this study are manufacturing companies listed on the Stock Exchange with the object of research is the practice of income smoothing and elements - elements that affect earnings. The population of 158 companies with logistic regression as the research method used in this study. The result of this research is ROA, OPM and leverage have no effect to the practice of income smoothing while firm size have an effect on Practice income smoothing significantly. Keywords: income smoothing, ROA, Return On Asset, OPM, Operating Profit Margin, Leverage, company size.